Especial skill vs. quiet eye duration in basketball free throw: Evidence for the inhibition of competing task solutions - Klostermann, A. (European Journal of Sport Science, 2019)
The quiet eye (QE) is a gaze phenomenon that has been studied over more than two decades. However, the underlying mechanisms of the well-known expertise effect, namely, longer QE durations in experts when compared to less-skilled athletes remain unclear. Therefore, from a functional perspective, an inhibition hypothesis was proposed that explains long QE durations in experts with increased inhibition requirements over movement parametrisation. This hypothesis was tested by making use of the especial-skill effect in basketball free throw which refers to the observation of higher actual performance than would be predicted on the basis of performance at the nearby locations. In line with the expectations, from the distance of the free-throw line, higher actual than predicted shooting accuracy and longer actual than predicted QE duration were revealed. This suggests that when performing free throws prolonged QE durations are required to shield the optimal against alternative task solutions within the very dense sub-space of this especial skill. These findings suggest an inhibition function of long QE durations in expert athletes.